2005
DOI: 10.1177/0887302x0502300415
|View full text |Cite
|
Sign up to set email alerts
|

Multimedia and Problem-Based Instruction in the Textiles Laboratory

Abstract: Historically, textile laboratory content has been delivered via a traditional approach called expository instruction and was designed to allow large numbers of students to perform activities simultaneously within a short time. An innovative learning method, problem-based learning (PBL), has been successful in teaching non-biological sciences. Evidence suggests multimedia learning environments facilitate the development of independent, self-regulated thinking. To evaluate the potential for PBL and multimedia as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
1
14
0
Order By: Relevance
“…PBL is a good fit in apparel design and merchandising coursework since the methodology is very ''hands-on.'' Farr, Ownbey, Branson, Cao, and Starr (2005) used a factorial analysis quasi experiment to analyze 155 students' responses. Students locate appropriate information and resources for solving their problem, with the instructor serving in an advisory role throughout the process.…”
Section: Pbl In Apparel Design and Merchandisingmentioning
confidence: 99%
“…PBL is a good fit in apparel design and merchandising coursework since the methodology is very ''hands-on.'' Farr, Ownbey, Branson, Cao, and Starr (2005) used a factorial analysis quasi experiment to analyze 155 students' responses. Students locate appropriate information and resources for solving their problem, with the instructor serving in an advisory role throughout the process.…”
Section: Pbl In Apparel Design and Merchandisingmentioning
confidence: 99%
“…Problem-based learning (PBL) or asking students to solve a problem is a constructivist approach that has been analysed in teaching apparel and textiles topics. PBL exercises related to teaching textiles include students examining experiments to learn about textiles science and students coordinating a sustainable fashion show (Farr, Ownbey, Branson, Cao, & Starr, 2005;Gam & Banning, 2011). These authors found PBL helped students learn, and students exhibited a high degree of motivation, engagement, and creative thinking.…”
Section: Constructivist Learning In the Apparel And Textiles Fieldmentioning
confidence: 99%
“…A constructivist teaching approach engages students and enhances their learning because it starts with what is already familiar to the students. This approach works particularly well if tangible objects and material are used (Marcketti, 2011), and it has been found to be a successful strategy to teach lessons related to history of fashion, textile science, and sustainable fashion (Farr et al, 2005;Gam & Banning, 2011;Marcketti, 2011). The research on fast fashion and apparel quality has been limited to examining the production of fast fashion that results in inexpensive and low-quality garments (e.g.…”
Section: Research Questionsmentioning
confidence: 99%
“…Cooperative learning strategies could be any activity that requires students to work as part of teams or groups at some point throughout the course, from period-long brainstorming sessions to semester-long projects. The most common collaborative teaching approach has been problem-based learning (PBL), used in teaching merchandising (Carpenter & Fairhurst, 2005), textiles (Farr et al, 2005), sustainable apparel design (Gam & Banning, 2011), and a capstone course comprised of merchandising, interior design, and graphic design majors (Kimmons & Spruiell, 2005).…”
Section: Review Of Literaturementioning
confidence: 99%
“…Potential challenges with this model are a lack of student motivation for the subject matter, lowered retention of key concepts, and limited understanding of how fashion history is applicable outside of a classroom (Marcketti, 2011). Recent research has highlighted the benefits of cooperative learning approaches to instruction in the undergraduate apparel classroom (Carpenter & Fairhurst, 2005; Farr, Ownbey, Branson, Cao, & Starr, 2005; Gam & Banning, 2011; Kimmons & Spruiell, 2005). While research has suggested numerous ways in which to teach courses in the apparel, merchandising, and design areas more effectively, none has specifically investigated the role that team-based learning (TBL) might play in teaching fashion history.…”
mentioning
confidence: 99%